Student Mobility Program Management System - MOHD YUSOFF, NUR SYAZWANI; IBRAHIM, DR NORAINI (Applied Information Technology And Computer Science, 2022)
The web system appears to be the current trend for the Student Mobility Program (SMP). In line with the Ministry’s aspiration to enhance internationalization of higher education, most universities and non-profit organizations are committed to help increase their student’s global mobility and provide opportunities for students to benefit from international travel. The goal of this project is to develop the Student Mobility Program Management System (SMPMS) within UTHM. Currently, the UTHM student mobility program is operated manually without a computerized system. There are certain problems that occur with present management that are, consume a lot of time and effort among mobility students and academic staff. In addition, the problem with the tedious process to submit the application and it is highly possible that the uploaded file was sent to the wrong person. These issues drive the development of SMPMS. It is developed through activities in the evolutionary software prototyping model where three iterations were involved. The SMPMS enables mobility students to submit their materials online. In addition, this system provides an important note or reminder, for instance, for the visa validation date. The system also allows mobility students to share their feedback or experiences when joining the mobility program. Apart from that, the system has been able to UTHM International Office to manage mobility programs, including the number of students participating and partner universities involved. Finally, it also produced a monthly and annual report to the International Office. The test result shows that the system passed 15 of the 15 test cases that represent 100% of all test cases. To conclude, this system is very useful for managing mobility programs effectively and efficiently, therefore, can increase the number of students joining UTHM mobility programs.